PENGARUH LEVERAGE, SIZE, DAN KEPEMILIKAN MANAJEMEN TERHADAP CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Almira Ma'rifati Robiah (AKUNTANSI DEWANTARA, 2017)
This research was motivated by the increasing linkages between social, environmental and business.               This study aimed to examine the effect of Leverage, Size, and ownership of the Corporate Social Responsibility Management Disclosure.The population in this study is the entire Manufacturing company is listed on the Indonesia Stock Exchange during the period from 2013 to 2015. The sample was Manufacturing Company follows industry sector consumption period 2013-2015. The sample is determined by purposive sampling in order to obtain 17 sample companies.Results of regression analysis showed that Leverage, Size and Management Ownership simultaneous positive influence on Corporate Social Responsibility Disclosure. Partially, Leverage and Management Ownership no significant effect on Corporate Social Responsibility Disclosure.whereas a significant positive effect Size Corporate Social Responsibility Disclosure. The third influence of independent variables on the dependent variable of 30.5% for the necessary additional variables in future studies. Keywords: Leverage, Size , earning management , Corporate Sosial Responbility Disclosure